Teaching english through grammar games in high school (young adults) - Bermeo Guiracocha, Patricio; Muñoz Castro, Fernanda
This project has the purpose of offering a sample of games as a contribution to the teaching-learning process in our high schools. The first part of this work presents a brief description of this study. Its main objective is to analyze students? needs in order to provide appropriate materials when learning English grammar. A survey was applied to pupils of 8th year of Basic Education of a night high school in Cuenca. The results showed that students? favorite skills and, at the same time, the most difficult ones to develop were reading, speaking and listening. Therefore, activities or games related with reading, speaking and listening were created so that students learn English easily and in an amusing way.